Optimal JPWL Forward Error Correction Rate Allocation for Robust JPEG 2000 Images and Video Streaming over Mobile Ad Hoc Networks. (6th July 2008) - Agueh Agueh, Max Max; Diouris Diouris, Jean-François Jean-François; Diop Diop, Magaye Magaye; Devaux Devaux, François-Olivier François-Olivier; De Vleeschouwer De Vleeschouwer, Christophe Christophe; Macq Macq, Benoit Benoit
Abstract : Based on the analysis of real mobile ad hoc network (MANET) traces, we derive in this paper an optimal wireless JPEG 2000 compliant forward error correction (FEC) rate allocation scheme for a robust streaming of images and videos over MANET. The packet-based proposed scheme has a low complexity and is compliant to JPWL, the 11th part of the JPEG 2000 standard. The effectiveness of the proposed method is evaluated using a wireless Motion JPEG 2000 client/server application; and the ability of the optimal scheme to guarantee quality of service (QoS) to wireless clients is demonstrated.